Metal–Organic Frameworks: Metal–Organic Frameworks Based on Group 3 and 4 Metals (Adv. Mater. 44/2020). Issue 44 (3rd November 2020) - Feng, Liang; Pang, Jiandong; She, Ping; Li, Jia‐Luo; Qin, Jun‐Sheng; Du, Dong‐Ying; Zhou, Hong‐Cai
Abstract : In article number 2004414, Jun‐Sheng Qin, Hong‐Cai Zhou, and co‐workers summarize the significant progress made in the rapidly developed field of metal–organic frameworks (MOFs) based on group 3 and 4 metals, and offer perspectives on the future trends of these robust MOFs. The novel properties and arising applications of these MOFs in catalysis, adsorption and separation, delivery, and sensing are highlighted.